Analysing of complementary perfect hop domination numeral of corona products of graphs. (16th December 2021) - Mahadevan, G.; Vijayalakshmi, V.
Recently, the authors introduced the concept of Complementary perfect hop domination number of a graph. A set S ⊆ V is a hop dominating set of G, if every vertex v ∈ V - S there exists u ∈ S such that d(u, v) = 2. A set S ⊆ V is said to be complementary perfect hop dominating set of G, if S is a hop dominating set and < V - S > has atleast one perfect matching. The minimum cardinality of complementary perfect hop dominating sets is called complementary perfect hop domination number of G and it is denoted by CPHD(G). In this paper we explore the CPHD number for the Corona product of two distinct paths and cycles.